SURVEY OF DENGUE KNOWLEDGE AND PREVENTION PRACTICES ASSOCIATED WITH SOCIODEMOGRAPHIC STATUS : A CROSS-SECTIONAL STUDY AMONG THE COMMUNITY LIVING IN AN URBAN AREA OF SELANGOR, MALAYSIA - Muhammad Aidil, Roslan; Romano, Ngui; Indra, Vythilingam; CHAN, KIEN FATT; ONG, POO SOON; LOW, CHING KEAT; NUR HIDAYAH, MUHAMED; Wan Yusoff, Wan Sulaiman (The American Mosquito Control Association, Inc., 2020)
The present study aimed to explore the current status of knowledge and practices of dengue prevention associated with sociodemographic status among the community living in an urban area of Selangor, Malaysia. A total of 441 participants were interviewed regarding sociodemographic status, knowledge of dengue, and self-reported prevention practices. Participants over 40 years old were more likely (odds ratio [OR] ¼ 4.210, 95% CI ¼ 1.652–10.733, P ¼ 0.003) to have better dengue knowledge. Participants whose average monthly household income was more than MYR3,000 (US$715) were more likely (OR ¼ 1.607, 95% CI ¼ 1.059–2.438, P ¼ 0.026) to have better practices of dengue prevention measures. The finding suggests that both government and community efforts are essential in order to continue to educate about dengue and reduce the frequency of dengue cases nationwide.